Role of HA additive in quantum dot solar cell with Co[(bpy)(3)](2+/3+)-based electrolyte - Chae, Sang Youn; Hwang, Yun Jeong; Joo, Oh-Shim (ROYAL SOC CHEMISTRY, 2014)
A strategy to improve the power conversion efficiency (eta) in a quantum dot solar cell (QDSC) is demonstrated with a model system of TiO2/CdS QDSCs. When the electrolyte is changed from polysulfide to a [Co(bpy)(3)](2+/3+) complex, a higher V-oc and eta are observed because of its low redox potential. To resolve the slow diffusion nature of [Co(bpy)(3)](2+/3+) complexes within dense TiO2 nanoparticle/CdS film, a TiO2 nanorod (NR) array anode is applied, which increases eta by more than a factor of 3. In addition, introduction of hexanoic acid (HA) in TiO2 NR/CdS film is found to improve eta (J(sc) as well as V-oc) by alleviating the back recombination loss between Co-III and the TiO2 surface. Electrochemical impedance spectroscopy indicates that the charge transfer resistance on the photoanode decreases by suppressing the interfacial charge recombination after HA treatment, although adding HA in the electrolyte impedes diffusion resistance.
Keywords: THIN-FILMS; ACID; RECOMBINATION; EFFICIENCY